Osimertinib administration via nasogastric tube in an EGFR‐T790M‐positive patient with leptomeningeal metastases. Issue 4 (2nd May 2017) - Takeda, Takayuki; Itano, Hideki; Takeuchi, Mayumi; Nishimi, Yurika; Saitoh, Masahiko; Takeda, Sorou
Abstract : Patients with an epidermal growth factor receptor (EGFR) mutation are usually administered EGFR‐tyrosine kinase inhibitors (TKIs) as standard‐of‐care treatment. However, acquired resistance occurs between 9 and 13 months. The T790M‐resistant mutations are the most common, and osimertinib has been found to be effective in treating EGFR‐T790M‐positive patients. A 73‐year‐old female lung cancer patient with an EGFR‐sensitizing mutation was receiving fourth‐line chemotherapy when she complained of anorexia, headache, and irritability. A lumbar puncture showed adenocarcinoma in the cerebrospinal fluid (CSF), which led to the diagnosis of leptomeningeal metastasis. Her performance status (PS) deteriorated quickly and she also developed dysphagia. The EGFR mutation testing of the CSF demonstrated L858R+T790M double mutations, and an osimertinib suspension was subsequently administered through a nasogastric tube. The PS improved to 1, oral intake became possible after 20 days, and further improvements were observed by gadolinium‐enhanced magnetic resonance imaging. The patient remains progression‐free for 10 months after osimertinib administration. Abstract : We present the case of a lung cancer patient with a diagnosis of leptomeningeal metastasis and epidermal growth factor receptor mutation (cerebrospinal fluid testing showed L858R + T790M double mutations), with poor performance status (PS) and dysphagia. Osimertinib suspension was administered through a nasogastric tube. PS improved to 1 with oral intake possible after 20 days and further improvements were observed by gadolinium‐enhanced magnetic resonance imaging. The patient remains progression‐free for 10 months after osimertinib administration.